CORRELAÇÕES GENÉTICAS E ANÁLISE DE TRILHA DE COMPONENTES DE PRODUÇÃO E PRODUTIVIDADE EM ACESSOS DE MAMONA - Douradinho, Gabriel; Paulino, Camilla; Bortolazzo, Guilherme; Limede, Arnaldo; De Freitas, Agner; Zoz, Tiago (ANAIS DO ENIC, 2018)
-